2015
DOI: 10.1787/5jrxhgf61q5j-en
|View full text |Cite
|
Sign up to set email alerts
|

Economic resilience: what role for policies?

Abstract: Complete document available on OLIS in its original format This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. ECO/WKP(2015)69 Unclassified English-Or. English ECO/WKP(2015)69 2 OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Reviews on specific policies for resilience to recessions are often done at the national level (Caldera Sanchez and Nicoletti, 2016 [21]; Röhn et al, 2015[22]; Caldera Sánchez, Rasmussen and Röhn, 2015 [8]). However, it is well acknowledged that recessions have differentiating impacts within countries, between demographic groups and places (Ahrend, Arnold and Moeser, 2011 [23]).…”
Section: Policies For Resilience To Recessions and Sector-specific Sh...mentioning
confidence: 99%
“…Reviews on specific policies for resilience to recessions are often done at the national level (Caldera Sanchez and Nicoletti, 2016 [21]; Röhn et al, 2015[22]; Caldera Sánchez, Rasmussen and Röhn, 2015 [8]). However, it is well acknowledged that recessions have differentiating impacts within countries, between demographic groups and places (Ahrend, Arnold and Moeser, 2011 [23]).…”
Section: Policies For Resilience To Recessions and Sector-specific Sh...mentioning
confidence: 99%
“…They can aim to be able to clearly identify and consistently track the business characteristics and performance of subpopulations of businesses that are of primary interest for business analysts and policymakers. To this end, very detailed analyses are needed to detect vulnerabilities, evaluate adjustment capability and structural change in an economic system, and assess the effectiveness of policy measures (Garda and Zieman 2014;Caldera et al 2015) that have an effect on identified sets (subdomains) of enterprises.…”
Section: Introductionmentioning
confidence: 99%